Well-posedness and regularity results for a dynamic Von Kármán plate - M. E. Bradley (International Journal of Mathematics and Mathematical Sciences)
We consider the problem of well-posedness and regularity of solutions for a dynamic von Kármán plate which is clamped along one portion of the boundary and which experiences boundary damping through free edge conditions on the remainder of the boundary. We prove the existence of unique strong solutions for this system